Conrad and Arendt. Revealing the roots of evil - Wiesław Ratajczak (Napis, 2022)
Titles of major works of both writers point to the effort of revealing the most difficult and most hidden knowledge of evil. Hannah Arendt, trying to excavate the roots (or rather, the beginnings) of totalitarianism, follows Joseph Conrad as an explorer of the kernel (or, more precisely: heart) of darkness. And when, later, Arendt embarks on a journey to Jerusalem to participate in the Eichmann trial, like Conrad’s Marlow, she is fascinated by tales of a strong man, because she expects to see someone undoubtedly bad, but also grand. Meanwhile, she reveals the ‘banality of evil’. This category is worth referring to in the case of Kurtz in Conrad’s story. The attacks of critics on Eichmann in Jerusalem, and Heart of Darkness, based on allegations of the humiliation of victims and suggesting their participation in the crime, also contain interesting parallels.